Mental Health Challenges in Women in Low- and Middle-Income Countries (LMICs): A Scoping Review - Aquartuti Tri Darmayanti; Joko Tri Atmojo; Aris Widiyanto; Hakim Anasulfalah; Ahmad Syauqi Mubarok; Atina Maya Fadhila (CV. Global Health Science Group, 2025)
Women are more likely than men to experience common mental disorders, especially in Low-Middle Income Countries (LMIC). Mental disorders contribute substantially to global disability. Overcoming this problem should be come to the priority. This review aims to synthesize the current understanding of the mental health challenges in women in low middle income country based on socioeconomic status, stigma, and integration with primary care. This scoping review was conducted following the framework outlined by Arksey and O'Malley. A literature search was conducted in the following databases: PubMed, Scopus, and Web of Science. Additionally, grey literature was searched through the World Health Organization and regional health ministries. Articles published since 2016-2026 were included. Keywords and phrases related to